Peningkatan Nilai Tambah Ekonomi Usaha Crisp Enye-Enye!! Kampung Cigundi dengan Pemanfaataan Teknologi - Miguna Astuti; Tati Handayani; Nurhafifah Matondang (Universitas Tidar, 2022)
Partners in this program are the PAGODA Women's Group in Cigundi Village, Cibadak District, Kab. Lebak-Banten. Lebak Regency is one of the regencies with the largest area in Banten Province. Based on data from the Agricultural Service of Lebak Banten Regency, Cibadak as one of the sub-districts has a high level of soil fertility. KWP members consisting of more than 20 housewives. So that it can be concluded in this PKM including (1) Increased partner capabilities by 75% related to making special packaging designs (packaging) by updating from the previous packaging to new packaging that is more specific and has a wide variety of colors to distinguish the type of taste it makes. (2) Partners are able to provide services through market places such as Tokopedia, with the Covid-19 pandemic not preventing KWP members from marketing these Crisp!! Enye-Enye products. At this stage it increased by 70% who previously did not really understand E-Commerce. (3) Apart from e-commerce, KWP members also partners are able to do digital marketing through Instagram, whatsapp and others at the digital marketing stage, an increase of 70% which previously only sold from whatsapp status, now they are starting to venture through Instagram.(4) By making new designs, providing good service and being active in digital marketing will make partners increase their income.The income per one-time production has increased to 150% only because the stock of raw materials is currently starting to be difficult to find in the Cigundi area which makes KWP members buy cassava at a lower price. different and the quality is different.